Learning experience of Quran memorization and etiquettes - Umar, Ronaldi Saleh; Nik Abdullah, Nik Md. Saiful Azizi; Nordin, Mohamad Sahari; Hashim, Sulaiman (Jabatan Multimedia KreatifFakulti Seni, Kelestarian dan Industri Kreatif Universiti, Pendidikan Sultan Idris Malaysia, 2023)
Quran memorization is a learning experience. To hearing the memorization is another experience. When someone learns to memorize Quranic verses, he/she needs to get an expert to listen and check on the memorization. This process is commonly called as Tasmi’, a meaningful teaching and learning process that can develop a great character to the Quran Care Taker (Hafz). This book elaborates the process of (i) before memorizing al Quran, (ii) during memorizing al Quran (iii) after memorizing al Quran, and Rubric on how to assess the Quran memorization. This book content is executed based on contents from PhD research. It suggests guidelines about assessing Quran memorization with etiquettes. It is hoped that this book can benefit anyone who has interest in Quran memorization, etiquette assessment, or any Hafz centers /schools who want to utilize the rubric to assess Hafz learners, in shaa Allah.